Metro Sisteminin Aydınlatılması - Baykal, Ebru (Fen Bilimleri Enstitüsü, 1997)
Bu tez çalışmasında, metropol hayatındaki ulaşım alanında büyük önem taşıyan metronun aydınlatma sisteminin önemi ve özellikleri hem estetik hem de işlevsel olarak incelenmiştir. Ayrıca işlenen konuyla ilgili karakteristik örneklere de yer verilmiştir. Birinci bölümde metro sisteminin şehir hayatındaki önemi ve aydınlatmanın bu sistem içindeki yeri incelenmiştir. İkinci bölümde metro sisteminin genel tanımı, metro sistemini oluşturan ana fonksiyonlar ve bu fonksiyonlara bağlı mekânların tanımları yapılmıştır. Üçüncü bölümde tanımlanan mekânlarda iyi aydınlatılmayı sağlamak için gerekli görsel gereksinimler ve aydınlatma tasarım kriterleri incelenmiştir. Seçilecek olan aydınlatma aygıtlarının, ışık kaynaklarının özellikleri, ışık kaynaklarının bakım ve temizlik ilkeleri incelenmiştir. Dördüncü bölümde yukarıda tanımlanan aydınlatma gereksinimleri ve tasarım kriterlerine bağlı olarak aydınlatma tasarımına yönelik öneriler geliştirilmiştir. Beşinci bölümde önerileri ve sonuçları destekleyen dünya metrolarından karakteristik örnekler sunulmuştur. Altıncı bölümde çalışmanın amaca uygunluğu ve sonuçları tartışılmıştır. Ekler bölümünde tasarım amaçlarına uygun olarak aydınlatma aygıtları ve ışık kaynakları dokümanlarına, katalog, teknik veri ve tablolara yer verilmiştir.

The light has been the most effective design tool and, for that matter, has been the favourite of the designers. The old designers have created silent works using stone, iron and light- Developments after Edison have provided the architects with ample opportunities. Artificial light sources are easy-to- control and are able to provide the internal spaces with stronger illumination. Lighting degrees and design targets must be considered within the limits of priorities and budget capacity. Thus, a lighting obtained by virtue of certain formulas as well as of numerical principles produces better results. The architectural importance of the lighting applied in the subways taking into consideration the user's needs and making use of technological developments is self-revealing in subway spaces of different functions. Main functions of the subway design can be grouped under six headings as transportation, passenger movement, technical service and parking functions. The spaces connected with these functions areas follows: Function Space Tunnels; If, when entered into the tunnel, the exit area is visible, then no artificial light is required. Otherwise, lighting must be taken into account. In- tunnel lighting values vary depending on the speed of vehicles. The level of lighting must be increased in parallel to the acceleration of speed. The level X1U of lighting to be supplied at the enterance of tunnel must be higher when the daylight is ample, and must be lower when the darkness has fallen (during the nightime). Such light must be controlled by means of a light control device. Such regulation can be made as follows: the lighting network is divided into 2 separate circuits and lower number of lamps are attached to the first circuit which will be on night and day while the second circuit should be fed from photocell and be regulated by the device depending on the level of daylight. A lighting of 100 lux is enough for nighttime lighting. The level of daytime lighting varies, however, depending on the level of daylight. Since daylight is accepted as 100 000 Luxes outdoor and as min. 10 000 Luxes indoor, 1/10 of daylight must be, then, used inside the tunnel; thaYs to say, minimum 1000 Luxes. Viaducts; concrete or steel posts must be used in lighting the viaducts and the fittings must be positioned 4 m above the level of pedestrian way. Viaduct lighting system must be fed equally from two stations. Stations; the lighting in stations must be positioned in such a way that it will improve the level of safety, security, comfort and beauty and that it will allow the passengers to walk easily. The level of station lighting must be relatively the same everywhere, but higher level of lighting must be provided in the functional places auch as ticket office or attention areas as well as in the platform borders, stairs and escalator landings for the emphasis thereof. Researchers conducted show that the light requirement in walking ways is min. 5 Luxes. This value enable the people stepping in the walking way to watch out their steps. Technical Services; The lighting in technical services must be positioned in such a way that it will allow the personnel to work comfortably and peacefully. Electrical equipment must, in general, be administered by means of switch panel located at the electricity room. External lighting must be administered by means of photocell, and must be controlled by means of photocell / time combination. Parking Lots; Lighting must be made by taking into consideration the safety and insularity factors. It is not easy to say that there is a standard lighting system for the lighting of parking lots which should be situated around the surtace station. Because their sizes and measurements are different. For example, in Washington subway, whole lighting has been positioned outside the parking lot and the lights have been directed at the parking lot (Figure 2.1). Thus, the outer environment has been left in the dark and the parking lot has enjoyed a distance visibility. Such an arrangement has given the chance of avoiding the difficulties relating to modular lighting in the places of different sizes but the same functions. Lighting has been supplied by means of quartz lamps. Such lamps are able to throw light towards the far in the distance in the form of strips. The lighting in ttie parking lot decreases as the people come nearer to the station and, thus, the lighting of station is underlined. XIV When lighting the underground stations, it is essential that the projects must be developed through co-operation of architectural designers and system engineers. Lighting in the stations must take into consideration the safety, security, comfort, utility, as well as the precautions aiming to increase the passenger circulation and to prevent sudden passages into dark fields from illuminated fields, the level of station lighting must be the same everywhere, however, higher level of lighting must be supplied to the ticket office, platform threshold, stairs and escalator landings. Lighting in the rail area must be minimum. The most important aim must be to enable the people to get rid of the fear of being inside a covered space. The hidden lighting of ceilings and walls is necessary for this purpose. Washington subway has been constructed with an arched ceiling and the lighting has been positioned under the floating platforms. Thus, sources of light has been hidden. The lighting in the rail areas has been supplied by means of sources placed under the flooring as well as of the sources placed between two rails. When any low level of lighting was involved, the roofs of ticket booths as well as the subway pylons used tor attaching announcement and direction plates have provided to be useful. The lighting has been supplied indirectly from the pylons. The pylons have been used as a ventilation condiut as well. Thus, they fulfilled two functions. Upward lighting from the pylons has been deemed more appropriate. Illuminated systems and illuminated warning signs used in cases of emergency: All stations and nonpublic places must be supplied with lighting by means of emergency illumination fed from separate sources and must be equipped with exit signs. Such illumination must be conforming to local codes and regulations, Surface stations must be lighted in such a way that the safety, comfort absolute visibility must be ensured. No additional lighting is required since the lighting provided for safety is, in general, higher than the minimum lighting requirement of the station. Abondant light gives birth to the concept of 'dangerous place, and the station loses its inviting look in the eyes of people residing around the station. By the selection of the lighting fittings and properties it must be taken into consideration that the selected fittings must be resistant to weather conditions. Any fittings which could resist wear and tear in damp and dusty environment must be selected. The fittings with protection class IP 65 are preferred. Both the in-fittings connections and the assembly details of the fittings must be able to resist the vibrations.
The Lighting Of Subway Systems
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1997
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1997
Keywords: Aydınlatma sistemleri; Metro; Lighting systemsü; Metro